Uses of the archive in exhibition practices of contemporary art institutions - Gul Durukan, S. Nesli; Tezcan Akmehmet, Kadriye (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
One area of increasing interest in contemporary art is the reconsideration and reinterpretation of archives to convey historical knowledge based on memory through exhibitions, organized by institutions. The aim of this paper is to contribute to a better understanding of how and why contemporary art institutions use archives in their exhibition practices. Six art institutions, which are members of L'Internationale, were sampled. Data from research demonstrated that contemporary art institutions organize archive-based art exhibitions to reinterpret the widely-known history; to reveal the lesser-known history; to fill in the gaps between artist, artwork, and institution; as a result of artists` archives and archive-based artworks and as an output of their research function. The paper argues that archive-based exhibitions provide a foundation for the new institutional activities and alternative interpretations out of the canonical history of art.
Keywords: Contemporary art; archive-based art exhibitions; art institutions; L'nternationale; Arts & Humanities - Other Topics